A review on oak decline: The global situation, causative factors, and new research approaches - KOWSARI, Mojegan; KARIMI, Ebrahim (Forest Systems, 2023)
Oak decline as a complex syndrome is one of the most relevant forest diseases worldwide. This disease has a complex and multifactorial nature, and this has caused conventional methods in plant pathology not to provide researchers with a correct and comprehensive analysis of oak decline. This issue entails the need for a multidisciplinary approach in examining and evaluating the disease, which will provide researchers with a more exhaustive understanding of the disease. The present review examines the concept of decline, the factors that contribute to the occurrence and development of the disease, its global distribution, and indexes used in the assessment of the disease. Furthermore, it draws attention to various research approaches that have been utilized to investigate oak decline.